Synthesis and characterization of 24‐membered cyclobis(ethylene 2, 6‐naphthalate). Issue 7 (22nd January 2020) - Xie, Donghang; Slebodnick, Carla; Gibson, Harry W.
Abstract: The pure 24‐membered cyclic dimer (2 ) of ethylene 2, 6‐naphthalate was isolated in 9% yield by reaction of bis(2′‐hydroxyethyl) 2, 6‐naphthalate (5 ) with 2, 6‐naphthalenedicarbonyl chloride (4 ) in THF with pyridine as catalyst under high dilution conditions. The macrocycle was characterized by NMR, MS, elemental analysis, and X‐ray crystallography. The crystal structure reveals a significant distortion of the naphthalene rings, forming an ellipsoidal cavity as a result of the ring strain, suggesting facile ring‐opening polymerization. Abstract : The pure 24‐membered cyclic dimer of ethylene 2, 6‐naphthalate was isolated in 9% yield after bis(20‐hydroxyethyl) 2, 6‐naphthalate reacting with 2, 6‐naphthalenedicarbonyl chloride in THF with pyridine as catalyst under high dilution conditions. The macrocycle was characterized using NMR, MS, elemental analysis, and X‐ray crystallography. The crystal structure reveals a significant distortion of the naphthalene rings, forming an ellipsoidal cavity as a result of the ring strain, suggesting facile ring‐opening polymerization.